ASSESSMENT OF PROFITABILITY OF WATER MELON (CITRILLUS LANATUS) IN SELECTED MARKETS IN PARTS OF KADUNA NORTHERN GUINEA SAVANNAH OF NIGERIA - Sodimu, A.I; Usman, M.B; Oladele, N.O; Lapkat, L.G.; Awobona, T.A; Suleiman, R (International Journal of Research -GRANTHAALAYAH, 2020)
The study examines the assessment of profitability of watermelon (Citrillus lanatus) in selected markets in parts of Kaduna Northern Guinea Savanna of Nigeria. One hundred questionnaires were randomly administered (100) and 51 were recovered from the respondents. Descriptive statistics gross margin analysis and Z- test were used to analyze the data collected. The results revealed that 74.51% of the respondents are male and 25.29% are female. Majority of the respondents are aged between 35 – 45 years (43.14%) and 12.55% are married. 35.29% of the respondent had secondary education and 39.21% had primary education. The gross margin analysis shows a significant level of profitability at (P>0.05) with estimated net income of #10,851.20 per annum. The Z- test further shows that the calculated value was statistically significant at (P>0.05) probability level. However, recommendation for improvement and marketing of the species were highlighted.